Factors Impacting the Academic Performance of Bangladeshi University Students - Amena Khatun (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study seeks to analyse the factors impacting the academic performance of Bangladeshi university students. Data were collected from 100 participants using the convenience sampling technique. Questionnaires have been used as research instruments. Microsoft Windows version 11 was used to complete the research writing and the Statistical Package for Social Sciences (SPSS) was used to analyse the data. The researcher performed a correlation study to investigate the relation between the independent and dependent variables. Regression analysis was performed to evaluate the impact of the independent factors on the dependent variable. Regression study demonstrated that personal factors, social factors and social media involvement significantly influence the suggested model. Institutional factors and curiosity have no any significant impact on academic performance. An artificial neural network was employed to examine the non-linear relationship among the variables. The study will help the students, guardians, academicians and policymakers to understand the factors impacting academic performance.